Analisis Arah Perkembangan Kawasan Permukiman di Negeri Negeri Lima - Fikram S. Watianan; Willem D. Nanlohy; Adnan Affan Akbar Botanri (ELASTICITY: Journal of Applied Engineering Science, 2024)
Negeri Lima is one of the countries in Leihitu District, Central Maluku Regency which has an area of 19 km2. On July 13, 2012, there was a mountain avalanche in Negeri Lima due to heavy rain that resulted in the closure of the river which resulted in the construction of the dam. A year later, the dam broke, and the water went directly towards the residents' settlements, destroying part of the residents' houses and infrastructure in Negeri Lima. Seeing the conditions as described, the fact of this research is how the direction of the development of residential areas in Negeri Lima, Leihitu District, Central Maluku Regency. This study aims to find out the direction of the development of residential areas in Negeri Lima, Leihitu District, Central Maluku Regency. The variables used in this study are related to the number of populations, the tragedy of the collapse of the Wae Ela Dam and changes in the location of residents' settlements. The analysis used in this study is by using two analyses, namely qualitative descriptive analysis, and spatial analysis (overlay). The results of data analysis show that settlements in Negeri Lima develop to the south and north of the country whose settlements are built following access to highways and coastal routes. But in the southern part of the country, settlement construction has a higher intensity. This is because many people whose houses were destroyed have land owned/inherited at that location